Arabic Dialects and Classical Arabic Language - Khrisat, Abdulhafeth Ali; Alharthy, Ziad Ali (Advances in Social Sciences Research Journal, 2015)
Classical Arabic (CA) is known as the language of the Qur’an. This form of Arabic language has been used among the people of different tribes of the Arabian Peninsula. Relations between these tribes were based on trade, marriage, war and poetry competition. The speakers of the tribes in Arabia have used different Arabic dialects. However, the dialect of the tribe of Quraish must have been like Classical Arabic. The study aims to prove that these old dialects of these tribes have not become remote and archaic but they have ensured their existence and continued to be used in many parts across the Arab world. Moreover, the article will identify the old different dialects of Arabic language and their characteristics and how they are related to the modern dialects in various Arab regions, with the exception of the arabized and borrowed words. In other words, modern Arabic dialects are rooted in the old dialects of Classical Arabic.